PENGARUH INTENSITAS PENGGUNAAN SMARTPHONE DAN SUMBER BELAJAR TERHADAP KEMAMPUAN KOGNITIF SISWA SMKS KRISTEN 2 TOMOHON - Kuhu, Fanly; Kambey, Joseph; Kandori, Iwan; Wokas, Starry (Literacy: Jurnal Pendidikan Ekonomi, 2024)
This research aims to determine the partial and simultaneous influence of the intensity of smartphone use and learning resources on the cognitive abilities of FASE E Class X and XI in SMKS Kristen 2 Tomohon students. This research method uses quantitative methods with multiple regression analysis with a total of 51 respondents, class X and XI FASE E students. The research results show that the t value for the intensity of Smartphone use is greater than the t table (3.675 > 1.677) while the t value for Learning Resources is also greater than the t table (2.034 > 1.677) where it can be concluded that there is a partially significant influence on the intensity of Smartphone use and learning resources on students' cognitive abilities, the simultaneous influence can be seen from the calculated f value where the calculated f is greater than f table (8.618> 3.19) meaning that there is a significant simultaneous influence on the intensity of smartphone use and learning resources on FASE students' cognitive abilities E Class X and XI at Christian Vocational School 2 Tomohon.